Office technology : developing skills in offce computing - Fairhurst, Maureen. (Nelson, 1993)
Introducing the chapter. Computers in the office. Computer hardware: systems unit components. Computer hardware: peripheral devices. Operating systems. Office productivity software. Communication systems. Care of the office computer system. Office automation. Ergonomics. Office equipment. Choosing your home computer.